Freakshow : first person media and factual television - Dovey, Jon (Pluto Press, 2000)
True confessions, fake films and docu-soaps - in the last ten years factual television has been transformed by an explosion of new genres. Freakshow offers a serious look at 'reality TV' in an attempt to understand the mass media's fascination with intimacy, deviancy, and horror. Jon Dovey analyses reality TV in terms of the political economy of the mass media. He investigates the relationship between confessional television and our modern understanding of culture and identity. Is our fascination with the personal the only meaningful response to the complexity of our own lives? Are the politics of the self the only alternative to the defunct grand narratives of yesterday? In concentrating not on the reception of these new television forms but on the choices, models and agendas which inform their production, Dovey reveals the relationships between social anxieties, economic pressures and their specific inflections in media texts. In a critical analysis of media industry practice, Dovey asks why directors can't stay out of range of their own cameras - and what is the role of the television of intimacy within broadcasting.